Metal organic frameworks as a corrosion inhibitor-highlighting their structural properties along with synthetic methods and its mechanism-A review - Sushmita; Jilna Jomy; Deepa Prabhu (Current Research in Green and Sustainable Chemistry)
Metal corrosion is an important concern for several industries, which results in large monetary damages and safety issues. Many inhibitors and strategies, like as coatings, electrochemical processes, and organic inhibitors, have been used to reduce corrosion. With their distinct structural and chemical characteristics that may be modified for uses, Metal-Organic Frameworks (MOFs) have become more desirable as a potential inhibitor of corrosion. The structural properties of MOFs are examined in this paper with a focus on corrosion prevention. Notable features include their high porosity, adjustable dispersion of corrosion inhibiting agents, chemical stability, and adherence to metal surfaces. The paper also includes the synthesis routes of MOFs and their historical evolution, comprising hydrothermal, room temperature, microwave, mechanochemical, sono-chemical, ultrasound-assisted, and electrochemical synthesis. Focusing on barrier formation, active inhibition, controlled release, and experiments in NaCl and acidic solutions, the mechanisms of corrosion inhibition by MOFs are also reviewed in this paper. By contrasting MOFs with conventional corrosion inhibitors, we talk about their benefits, drawbacks, and possible uses. The paper concludes with a discussion of challenges faced in the practical application of MOFs for corrosion prevention as well as future research directions.